How are you peeling?: Foods with moods - Freymann, Saxton; Elffers, Joost (New York : Scholastic, 1999)
Brief text and photographs of carvings made from vegetables introduce the world of emotions by presenting leading questions such as "Are you feeling angry?"
F
370
F
Keywords: Fruit; Vegetable